Wintertime Atmospheric Response to North Atlantic Ocean Circulation Variability in a Climate Model - Frankignoul, Claude; Gastineau, Guillaume; Kwon, Young-Oh (Journal of Climate, 2015)
International audience Maximum covariance analysis of a preindustrial control simulation of the NCAR Community Climate System Model, version 4 (CCSM4), shows that a barotropic signal in winter broadly resembling a negative phase of the North Atlantic Oscillation (NAO) follows an intensification of the Atlantic meridional overturning circulation (AMOC) by about 7 yr. The delay is due to the cyclonic propagation along the North Atlantic Current (NAC) and the subpolar gyre of a SST warming linked to a northward shift and in-tensification of the NAC, together with an increasing SST cooling linked to increasing southward advection of subpolar water along the western boundary and a southward shift of the Gulf Stream (GS). These changes result in a meridional SST dipole, which follows the AMOC intensification after 6 or 7 yr. The SST changes were initiated by the strengthening of the western subpolar gyre and by bottom torque at the crossover of the deep branches of the AMOC with the NAC on the western flank of the Mid-Atlantic Ridge and the GS near the Tail of the Grand Banks, respectively. The heat flux damping of the SST dipole shifts the region of maximum atmospheric transient eddy growth southward, leading to a negative NAO-like response. No significant atmospheric response is found to the Atlantic multidecadal oscillation (AMO), which is broadly realistic but shifted south and associated with a much weaker meridional SST gradient than the AMOC fingerprint. Nonetheless, the wintertime atmospheric response to the AMOC shows some similarity with the observed response to the AMO, suggesting that the ocean–atmosphere interactions are broadly realistic in CCSM4.